Modeling of inter- and intra-particle coating uniformity in a Wurster fluidized bed by a coupled CFD-DEM-Monte Carlo approach - Jiang, Zhaochen; Rieck, Christian; Bück, Andreas; Tsotsas, Evangelos (Chemical Engineering Science, 2020)
A coupled CFD-DEM and Monte Carlo approach was developed to investigate coating properties in a Wurster fluidized bed by considering gas flow, particle motion, droplet deposition, and the drying and solidifying of droplets on particle surfaces. Based on the spherical centroidal Voronoi tessellation (CVT), the Monte Carlo approach can model the deposition and splashing of spray droplets on the surface of individual particles. The capillary force induced by liquid bridges between particles was accounted in the DEM to investigate its influence on the coating and agglomeration behavior. The new model can provide information about the cycle time distribution, residence time distribution, coating coverage, uniformity of porosity (influenced by splashing) and layer thickness distributions on each individual particle (intra-particle) and in the particle population (inter-particle). The simulation results are compared with experimental data on residence time and intra-particle layer thickness distributions. Good agreement is observed between the simulation and the measurements.
CRIS-Team Scopus Importer:2019-10-29
Keywords: CFD-DEM; Coating; Monte Carlo; Surface coverage; Wurster fluidized bed